Assembly processes of rhizosphere and phyllosphere bacterial communities in constructed wetlands created via transformation of rice paddies - Deng, Nan; Liu, Caixia; Tian, Yuxin; Song, Qingan; Niu, Yandong; Ma, Fengfeng (Frontiers in Microbiology, 2024)
Constructed wetlands are an efficient and cost-effective method of restoring the degraded wetlands, wherein the microorganisms make a significant contribution to the ecosystem. In this study, we comprehensively investigated the diversity patterns and assembly processes of 7 types of constructed wetlands at the rhizosphere and phyllosphere levels. The results showed that the rhizosphere communities of the constructed wetlands exhibited a more balanced structure than that of paddy fields, and 5 constructed wetland types presented a higher potential diversity than that of paddy fields.However, the phyllosphere communities showed an opposite trend. The analysis of MNTD indicated that both deterministic and stochastic processes affected the establishment of the rhizosphere and phyllosphere communities, and stochastic processes may have a greater effect. iCAMP model showed that the dispersal limitation was the most important (67%) in the rhizosphere community, while the drift was the most important (47%) in the phyllosphere community. Mantel test suggested that sucrase, average height, top height, total biomass, belowground biomass, maximum water holding capacity and capillary porosity were significantly correlated with the rhizosphere community, whereas the factors like the deterministic process, average height, top height and SOC were significantly correlated with phyllosphere community deterministic process. Our results can assist to evaluate the artificial restoration, understand the ecological processes of the microbial community, and provide new insights into the manipulation of microorganisms in the polluted wetland ecosystems.